Fecal galectin-1 as a potential marker for colorectal cancer and disease severity - Jovanovic, Milan; Gajovic, Nevena; Zdravkovic, Natasa; Jovanovic, Marina; Jurisevic, Milena; Vojvodic, Danilo; Mirkovic, Darko; Milev, Bosko; Maric, Veljko; Arsenijevic, Nebojsa (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Colorectal cancer (CRC) represents one of the most common cancers worldwide. CRC is frequently diagnosed at advanced stages with poor prognosis, indicating the need for new diagnostic and prognostic markers. The aim of this study was to determine systemic and fecal values of galectin-1 (gal-1) and ratios between gal-1 and proinflammatory cytokines: tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β) and interferon gamma (IFN-γ), in the patients with CRC and the relationship with clinicopathological aspects of the disease. Methods. The blood samples and feces liquid fraction of 58 patients with CRC were analyzed. The serum and fecal levels of TNF-α, IL-1β and IFN-γ and gal-1 were measured using sensitive enzyme-linked immunosorbent assay (ELISA) kits. Results. The fecal level of gal-1 was increased in the CRC patients with higher nuclear grade and poor tumor tissue differentiation. The gal-1/TNF-α ratio in the serum and feces had a higher trend in the patients with the advanced tumor-node-metastasis (TNM) stage as well as the detectable lymphatic and blood vessel invasion. The gal-1/TNF-α and gal-1/IFN-γ ratios were increased in the serum of patients with presence of lung/liver metastasis or peritoneal carcinomatosis, while the enhanced gal-1/IL-1 ratio was detected only in the serum of patients with lung metastasis. A positive correlation between the gal-1 value in feces and histological differentiation of tumor and biomarkers alpha-fetoprotein (AFP) and cancer antigen-19-9 (CA 19-9), respectively, was also observed. The fecal values of gal-1 higher than 13,708.29 pg/g presented a highly sensitive and specific marker for histological differentiation of tumor tissue. Conclusion. We believe that the predomination of gal-1 over pro-inflammatory cytokines TNF-α, IL-1β and IFN-γ in the patients with advanced and progressive CRC may implicate on an immunomodulatory role of gal-1 in the limiting ongoing proinflammatory processes. The fecal values of gal-1 can be used as a valuable marker for the severity of CRC.
Keywords: colorectal neoplasms; carcinoma; feces; galectin-1; disease progression